The Relationship Between Knowledge Of Primigravida Pregnant Women About Preeclampsia And Early Detection Of Preeclampsia - Lilik Darwati (Journal for Quality in Women's Health, 2025)
The death rate for pregnant women due to preeclampsia and eclampsia in developing countries is still high. The frequency of preeclampsia, especially for young primigravidas, is higher than for multigravidas. The aim is to increase knowledge about early detection of preeclampsia in pregnant women, which is very important for carrying out fast and appropriate treatment, especially in primigravida pregnant women. This research is a quantitative descriptive study with a cross sectional approach.